Determinants of the little auk (Alle alle) breeding colony location and size in W and NW coast of Spitsbergen - Keslinka, Liliana Katarzyna (PLoS One, 2019)
Many seabirds breed in large aggregations, making it difficult to estimate their population size and habitat preferences. This knowledge is particularly important considering their function in food webs and ecosystem services. In this study, we investigated the factors affecting distribution and abundance of the little auk Alle alle, a seabird considered a keystone species of the Arctic ecosystem. We performed the study on the W and the NW coast of Spitsbergen. Using Generalized Additive Models (GAMs) and Conditional Inference Tree (CIT) we examined factors related to presence/absence and size (estimated number of breeding pairs) of the little auk colonies. We also tested the nesting preferences for geographical features such as aspect, slope angle, altitude, solar radiation, rock type, and distance to foraging grounds. Our findings indicate that the occurrence of little auk breeding colonies is non-random and highly attributed to environmental factors. The probability of colony occurrence was significantly associated with altitude (negative relationship; preference to sites situated lower), solar radiation (positive relationship; the higher radiation, the more likely colony occurrence) and slope (positive relationship; the steeper a slope, the more likely colony occurrence), whilst aspect appeared non-significant (though the probability of colony occurrence peaked at southern slopes). Colony size was significantly associated with rock type (larger colonies in amphibolite and quartzite). The distance to foraging grounds did not appear to affect the probability of colony occurrence and size, implying that birds may choose optimal breeding sites at the cost of longer foraging flights. We estimated the Spitsbergen little auk breeding population at 728 529 (5–95% CI: 479 312–986 352). Spitsbergen comprises ca 1.9% (95% CI: 1.2%–2.7%) of the world breeding population and represents the third most important breeding area for the species, following the W and the E coast of Greenland.